Cognitive spare capacity in older adults with hearing loss - Mishra, Sushmit; Stenfelt, Stefan; Lunner, Thomas; Rönnberg, Jerker; Rudner, Mary (Frontiers in Aging Neuroscience, 2014)
Individual differences in working memory capacity are associated with speech recognition in adverse conditions, reflecting the need to maintain and process speech fragments until lexical access can be achieved. When working memory resources are engaged in unlocking the lexicon, there is less Cognitive Spare Capacity (CSC) available for higher level processing of speech. CSC is essential for interpreting the linguistic content of speech input and preparing an appropriate response, that is, engaging in conversation. Previously, we showed, using a Cognitive Spare Capacity Test (CSCT) that in young adults with normal hearing, CSC was not generally related to working memory capacity (WMC) and that when CSC decreased in noise it could be restored by visual cues. In the present study, we investigated CSC in 24 older adults with age-related hearing loss, by administering the CSC Test (CSCT) and a battery of cognitive tests. We found generally reduced CSC in older adults with hearing loss compared to the younger group in our previous study, probably because they had poorer cognitive skills and deployed them differently. Importantly, CSC was not reduced in the older group when listening conditions were optimal. Visual cues improved CSC more for this group than for the younger group in our previous study. CSC of older adults with hearing loss was not generally related to WMC but it was consistently related to episodic long term memory, suggesting that the efficiency of this processing bottleneck is important for executive processing of speech in this group.